Phenotypic and genetic differentiation between diadromous and landlocked puyen Galaxias maculatus - Rojo, Javier Hernán; Fernandez, Daniel Alfredo; Figueroa, Daniel Enrique; Boy, Claudia Clementina (Journal of Fish Biology)
This study reports the phenotypic and genetic differences between individuals of puyen Galaxias maculatus from two sites in the same river basin in Tierra del Fuego National Park, southern South America. Individuals from the two sampling sites presented morphometric and genetic differences. The morphometric differences indicated that individuals from Laguna Negra (LN) were short and more robust and had large eyes, whereas those from Arroyo Negro (AN) were thin and elongated and had small eyes. Genetic differences showed that AN individuals had a greater genetic structuration and an older demographic history than LN individuals. The results of this study affirmed that the individuals from the two sampling sites belong to different populations with a high degree of isolation. The demographic history could indicate that the individuals of G. maculatus which migrated to northern areas during the last glaciation settled in the Beagle Channel after its formation. The LN population could have originated after the retreat of the glaciers, migrating from AN. Fil: Rojo, Javier Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Fernandez, Daniel Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Figueroa, Daniel Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina